Development of Choco Banana Bread as a Source of Dietary Fiber Using Beneng Taro Flour and Rice Bran - Mia Mustika Hutria Utami; Ksatriadi Widya Dwinugraha; Annisa Rizkiriani; Zakiya Dwi Rara (Universitas Negeri Padang, 2026)
The high consumption of low-fiber sweet bread based on wheat flour in Indonesia and the dependence on wheat imports encourages innovation in bakery products using local fiber sources. This study aims to develop choco banana bread as a fiber-based food by substituting wheat flour with a composite of rice bran and beneng taro flour, evaluating its sensory quality and nutritional content. Experimental research using a Completely Randomized Design with three formulas, each containing 70% wheat flour and 30% composite flour with a ratio of rice bran: beneng taro F1 (65%:35%), F2 (50%:50%), and F3 (35%:65%). Sensory evaluation by 35 semi-trained panelists using hedonic tests (appearance, color, aroma, texture, taste, overall acceptance) and hedonic quality (color, taste, aroma, texture, mouthfeel) showed that F3 was the best formula based on the Exponential Comparison Method; The hedonic test showed significant differences (p<0.05) in appearance, color, aroma, and overall acceptability with F3 obtaining the highest score, while texture, taste, and other hedonic quality test parameters did not differ significantly (p≥0.05). F3 (60 g/serving) contains 204 kcal, 5.1 g protein, 7.9 g fat, 28.3 g carbohydrate, and 8.8 g dietary fiber, thus fulfilling the claim as a fiber-rich food, containing 1.5 times more protein, and 7 times more dietary fiber than commercial products. These findings indicate that rice bran and taro have the potential to produce fiber-rich bread with sensory qualities acceptable to consumers, supporting food diversification, and reducing dependence on wheat imports.